Production, Consumption, Export and Carbon Emission for Coal Commodities: Cases of Indonesia and Australia - Aimon, Hasdi; Kurniadi, Anggi Putri; Sentosa, Sri Ulfa; Rahman, Nurhayati Abd (International Journal of Energy Economics and Policy, 2023)
The contribution of this study is to analyze the impact of a series of economic activities from the coal commodity on carbon emission. This research specifically focuses on coal exporting countries in Asia Pacific, including Indonesia and Australia during the period 2000 to 2022. The purpose of this study is to investigate the influence between production, consumption and export of coal and its determinants, and also the effect on carbon emission. This study applies the simultaneous equation approach and panel regression. The main findings of this study are that coal consumption, coal export, technological innovation and coal price have a positive and significant effect on coal production. Furthermore, coal production, domestic income and domestic investment have a positive and significant effect on coal consumption, while coal export has a negative and significant effect. Then, coal production and coal stock have a positive and significant effect on coal export, while coal consumption and domestic investment have a negative and significant effect. Finally, production, consumption and export of coal commodities contribute to increasing carbon emission. We recommend the coal exporting countries analyzed in this study to implement coal energy control in addressing increasing carbon emission at the global level.